The venom gland transcriptome of Tityus paraguayensis reveals a diverse array of bioactive molecules from the Brazilian Cerrado - Henrique Ranieri Covali-Pontes; Brayhan Meneguelli; Jéssica de Moraes Carretone; Alynne Coelho Ribeiro; Angélica Camargo dos Santos; Thais Fernanda Carlos; Marcos Roberto Chiaratti; Milene Ferro; Flávio Henrique Silva; Renata dos Santos Rodrigues; Malson Neilson Lucena (PLoS ONE, 2026)
Scorpions are arthropods with venom glands at their telson that produce chemicals such as peptides and proteins. These compounds may have pharmacological effects, including antimicrobial, ion channel modulating, and antihypertensive activities. Our study aims to examine the transcripts from the venom glands of Tityus paraguayensis , focusing on identifying and annotating the genes expressed in these glands. A transcript encoding a potassium channel-modulating peptide was selected for 3D structural modeling, phylogenetic analysis, and interaction assessment. Initially, the scorpions’ telsons were dissected and analyzed using transcriptome sequencing. The data were then assembled and functionally annotated. The sequencing and assembly of the venom gland transcriptome produced a set of 37,283 transcripts, of which 523 were annotated as potentially related to venom components. Among the venom components, peptides that modulate sodium (8%), potassium (9%), and calcium (1%) channels, antimicrobial peptides (6%), antihypertensives (2%), phospholipases (1%), and metalloproteinases (29%) were identified, along with other compounds (44%). Specific highlights include the structural-functional analysis of four key peptides: TpNa3, a probable β-toxin sodium channel modulator with a βαββ structural motif; TpHyp1, a long-chain antihypertensive peptide that contains the conserved KPP motif; TpAP1, a short antimicrobial peptide with a low positive charge and an α-helical structure; and TpK8 is a potassium toxin that was previously partly identified (α-KTx). Molecular modeling and docking analyses showed that TpK8 binds with high affinity and stability, especially to the Kv1.3 channel, through specific interactions with the selectivity filter. These findings emphasize the extensive molecular diversity of T. paraguayensis venom, highlighting its potential as a rich and largely unexplored source of bioactive molecules. This makes it a promising target for developing new bioactive compounds for biotechnological and therapeutic use.